ORCA: architecture for business tier components driven by dynamic adaptation and based on call level interfaces - Pereira, Óscar Narciso Mortágua
Call Level Interfaces (CLI) play a key role in database applications whenever performance is a key requirement. SQL statements are encoded inside strings this way keeping the power and the expressiveness of the SQL language. Unfortunately, despite this significant advantage, CLI do not promote the development of business tier components, much less for business tier components driven by dynamic adaptation. To tackle this CLI drawback, and simultaneously keep their advantages, this paper proposes an architecture, herein referred to as the Object-to-Relational Component Architecture (ORCA), relying on CLI for building adaptable business tiers components. ORCA has the capacity of being dynamically adapted to manage any set of SQL statements deployed at runtime. The focus of this paper is threefold: 1) present the ORCA, 2) present a proof of concept based on Java and, finally, 3) assess its performance against a standard CLI.